Análise das teleconsultorias odontológicas do Telessaúde Núcleos Minas Gerais - Ligia Cristelli da Paixao (2018)
This cross-sectional study aimed to evaluate the off-line dental teleconsulting of Telehealth Brazil Networks Program in Minas Gerais state Telehealth centers, with emphasis in Endodontics. Data were collected from secondary databases of the Clinical Hospital of the Federal University of Minas Gerais (CH/UFMG) and Medical School of UFMG (MS/UFMG), from July 2015 to July 2017. The variables analyzed were telehealth center; applicants gender and profession; date and time of question and answer; response time in days; if the issue was duly answered; if teleconsulting was attended; posting status; professionals satisfaction; conduct adopted after teleconsulting; dental specialty area and subarea and type of issues. Sociodemographic data from the Intermediate Geographical Regions (IGR) of Minas Gerais, the Municipal Human Development Index (MHDI) and Gini Index were also collected. The results were descriptively analyzed using SPSS v.22.0. In total, 3,920 teleconsulting sessions were recorded, with increasing demand in the period (n=187 from July to December 2015; n=2,214 in 2016 and; n=1,519 from January to July 2017). Most were demanded by dentists (93.3%) and female (78.6%) professionals, during office hours (78.6%) and related to general conducts, with doubts related to treatment, prevention and preservation of oral conditions (72.1%). Almost all were attended (99.7%), with a maximum response time of two days (75.0%). There was low feedback regarding satisfaction and resolution of issues (57.2% and 70.2%, respectively, without information). Only 5.2% had information on whether patients were referred. The higher prevalence of issues related to Pathology/Stomatology specialties (19.0%), followed by Pharmacology/Anesthesiology (18.8%), Pediatric Dentistry (10.3%), Surgery (10.2%), Dentistry/Prosthesis (8.6%) and Endodontics (7.4%). The response occurred within the expected time, with the prevalence of issues in primary dental areas and general conducts. The most prevalent Endodontic doubts were related to pulp and periapical alterations (32.3%), dental trauma (15.6%), endodontic urgencies (11.4%) and intracanal medication (7.3%). The basic areas should receive a greater emphasis on undergraduate courses, to better prepare professionals for clinical practice and determine the adequate diagnosis and integral treatment to the patient. The most prevalent endodontic doubts were related to the daily challenges of Primary Health Care (PHC) professionals. It is of fundamental importance the continuous updating of the professionals, both through continuing education programs and through the search for new knowledge, promoting a reinforcement of these competences. In addition, applicants feedback needs to be encouraged to allow better analysis and improvements to the program.